PELATIHAN BRANDING PRODUK UMKM BAGI WARGA KELURAHAN MULYO JATI KOTA METRO - Abdi Darmawan; Ade Moussadecq; Rohiman Rohiman; Hendra Kurniawan (Institut Informatika dan Bisnis Darmajaya, 2022)
The Community Service Team (PKM) of the Visual Communication Design Study Program has carried out PKM activities in Mulyojati Village, Metro City with a focus on service in the form of branding MSME products for residents of Metro City Urban Village. The importance of the role of product branding in a marketing activity is the background of this activity. The brand of a product will be easily remembered by potential consumers because of the emotions and imagination of consumers (brand awareness) that arise due to the impact of the branding. The method applied in this activity is the Presentation Method regarding the definition, function, purpose, and benefits of product branding. After completing the presentation, the service team conducted an evaluation in the form of a partner understanding survey regarding branding before and before the activity.